Prey use by dingoes in a contested landscape: Ecosystem service provider or biodiversity threat?. Issue 21 (21st September 2017) - Morrant, Damian S.; Wurster, Christopher M.; Johnson, Christopher N.; Butler, James R. A.; Congdon, Bradley C.
Abstract: In Australia, dingoes ( Canis lupus dingo ) have been implicated in the decline and extinction of a number of vertebrate species. The lowland Wet Tropics of Queensland, Australia is a biologically rich area with many species of rainforest‐restricted vertebrates that could be threatened by dingoes; however, the ecological impacts of dingoes in this region are poorly understood. We determined the potential threat posed by dingoes to native vertebrates in the lowland Wet Tropics using dingo scat/stomach content and stable isotope analyses of hair from dingoes and potential prey species. Common mammals dominated dingo diets. We found no evidence of predation on threatened taxa or rainforest specialists within our study areas. The most significant prey species were northern brown bandicoots ( Isoodon macrourus ), canefield rats ( Rattus sordidus ), and agile wallabies ( Macropus agilis ). All are common species associated with relatively open grass/woodland habitats. Stable isotope analysis suggested that prey species sourced their nutrients primarily from open habitats and that prey choice, as identified by scat/stomach analysis alone, was a poor indicator of primary foraging habitats. In general, we find that prey use by dingoes in the lowland Wet Tropics does not pose a major threat to native and/or threatened fauna, including rainforest specialists. In fact, our results suggest that dingo predation on "pest" species may represent an important ecological service that outweighs potential biodiversity threats. A more targeted approach to managing wild canids is needed if the ecosystem services they provide in these contested landscapes are to be maintained, while simultaneously avoiding negative conservation or economic impacts. Abstract : We determined the potential threat posed by dingoes to native vertebrates in Australia's lowland Wet Tropics using dingo scat/stomach content and stable isotope analyses. In general, we found that prey use by dingoes in the region does not pose a major threat to native and/or threatened fauna, including rainforest specialists. Alternatively, our results suggest that dingo predation on "pest" species may represent an important ecological service that outweighs potential biodiversity threats.